Association between the triglyceride glucose index and long-term outcomes in patients with acute coronary syndrome and chronic kidney disease - Feng Wang; Wendi Huang; Chonghao Shi; Yongfu Zhu; Weicheng Ni (Diabetology & Metabolic Syndrome)
Abstract Background Despite the association between the triglyceride-glucose (TyG) index and major adverse cardiovascular events (MACE) has been reported, a notable research gap persists regarding its predictive value in patients with acute coronary syndrome (ACS) and chronic kidney disease (CKD). This study endeavors to bridge this gap by investigating the relationship between the TyG index and outcomes among this unique patient cohort. Methods Patients having ACS with CKD were recruited from January 2013 to December 2021. Outcomes included all-cause mortality and MACE. The potential linear relationship was visualized by the restricted cubic spline (RCS) curve. Cox proportional hazards models were employed to rigorously examine the association between the TyG index and study outcomes. Furthermore, to assess the incremental value of the TyG index, we conducted analyses using C-statistics, the continuous net reclassification index (cNRI), and the integrated discrimination index (IDI). Results A total of 1094 patients were included in the final analysis. Over a median follow-up period of 30.1 months (IQR: 16.5 to 40.0 months), we recorded 167 (15.3%) all-cause mortality events and 285 (26.1%) MACE. Additionally, each 1-unit increase of it was significantly associated with a 61% elevation in the risk of all-cause mortality (95% CI: 1.28–2.03, P < 0.001) and a 72% increase in the risk of MACE (95% CI: 1.45–2.05, P < 0.001). These associations between TyG index (as quantitative or categorical variables) and endpoints remained robust even after multivariable adjustment. RCS analysis showed linear relationships between TyG and endpoints (all P for non-linear > 0.05). Moreover, subgroup analysis revealed significant interactions of dialysis and renal function (P for interaction = 0.008 and 0.011, respectively) with all-cause mortality. Lastly, combining with the established risk score significantly enhanced the discrimination and reclassification performance of TyG, as evidenced by the C-statistic, cNRI, and IDI values (all P < 0.05). Conclusion For patients with both ACS and CKD, TyG index is associated with both MACE and all-cause death. Prognostic classification is enhanced by the TyG index. The results collectively suggest that the TyG index serves as a reliable predictor of outcomes among patients with ACS and CKD, offering a novel metabolic perspective.